2020
DOI: 10.1088/1757-899x/861/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

Modelling viscoplastic behavior of solidifying shell under applied electromagnetic breaking during continuous casting

Abstract: Since several decades the continuous casting (CC) process became one of the dominant technologies for the metal production. The quality optimization and the production rate growth are the primary targets. Nowadays the numerical modelling is a valuable tool to assist in these aims. Moreover, it efficiently competes with the physical experiment and the industrial trials. One of the key issues with the high casting speeds especially for the thin slab products are the strong turbulent flow of the fresh melt being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…While there seems to be some success in the case of the horizontal EMBr, the authors surprisingly failed to show a way to prevent or control the DD phenomenon using the vertical EMBr. Recently, Vakhrushev et al [22] took both the viscoplastic behavior of the solidified shell and the magnetohydrodynamics (MHD) effects of the EMBr into account to simulate the turbulent flow and the shell thickness during the thin slab casting with and without the DC magnetic field.…”
Section: Ensuring the Quality Of Continuous Cast (Cc)mentioning
confidence: 99%
“…While there seems to be some success in the case of the horizontal EMBr, the authors surprisingly failed to show a way to prevent or control the DD phenomenon using the vertical EMBr. Recently, Vakhrushev et al [22] took both the viscoplastic behavior of the solidified shell and the magnetohydrodynamics (MHD) effects of the EMBr into account to simulate the turbulent flow and the shell thickness during the thin slab casting with and without the DC magnetic field.…”
Section: Ensuring the Quality Of Continuous Cast (Cc)mentioning
confidence: 99%
“…The thermophysical parameters can be calculated according to the expressions in [44]. The electrical conductivity of solid steel was assumed to be 1.4 times the electrical conductivity of liquid steel [28]. The simulated material parameters are listed in Table 3.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…A typical way to calculate solidification is the enthalpy-porosity method. Vakhrushev [26][27][28] calculated the motion of the solidified shell by an incompressible rigid viscoplastic model. The results showed that neglecting advective latent heat due to the motion of the solidified shell might lead to overestimating the shell thickness.…”
Section: Introductionmentioning
confidence: 99%
“…First, the averaged ratio between the liquid and solid electric conductivities is plotted in Figure 16(a) in the left curve, which is derived here from the extended data for different AISI steel grades, reported in 1978 by Chu and Ho. [44] The right curve in Figure 16(a) shows slab surface temperature along the mold's wide face, simulated by Vakhrushev et al [45,46] The corresponding thickness (100 pct of solid, top picture) and the conductance ratio (bottom picture) of the solid shell are plotted in Figure 16(b), which are obtained from the thin slab simulations [45,46] and calculated for the 72-mm-thick slab using Eq. [19] based on the temperature-dependent electric conductivity (see Figure 16(a)).…”
Section: Application To Continuous Castingmentioning
confidence: 99%
“…[Chu & Ho 1978] wide face m m Fig. 16-Solid shell conductance ratio for the thin slab casting: (a) averaged temperature-dependent ratio r sol =r liq (from Chu and Ho 1978) [44] and surface temperature T surf for the 72-mm-thin slab (Vakhrushev et al); [45,46] (b) simulated shell thickness (top); and its conductance ratio (bottom).…”
Section: (A) (B)mentioning
confidence: 99%